Family and the state in early modern revenge drama : economies of vengeance - McMahon, Chris (Routledge studies in Renaissance literature and culture., 2012)
In this book, McMahon considers Early Modern revenge plays from a political science perspective, paying particular attention to the construction of family and state institutions. Plays set for close study are The Spanish Tragedy, Hamlet, The Revenger's Tragedy, The Malcontent and The Duchess of Malfi. The plays are read as unique events occupying positions in historical process concerning the privatisation of the family (by means of symbolism and concrete household strategies such as budgeting and surveillance) and the subsequent appropriation of the family and its methods.